2019
DOI: 10.12659/msm.912412
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-744 Inhibits Proliferation of Bronchial Epithelial Cells by Regulating Smad3 Pathway via Targeting Transforming Growth Factor-β1 (TGF-β1) in Severe Asthma

Abstract: Background Bronchial epithelial cells proliferation plays a pivotal role in airway remodeling in children with severe asthma. MicroRNAs (miRNAs) have gained great attention for many diseases, including asthma. The purpose of this study was to explore the mechanisms that underlie miR-744 modulating bronchial epithelial cells proliferation in severe asthma in children. Material/Methods Bronchial epithelial cells were isolated from bronchial biopsies of normal controls and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Nonetheless, the following are studies that emerged in recent months. In severe asthmatic bronchial epithelial cells obtained from patients, the level of miR-744 was decreased compared to its expression in normal control cells [61]. miR-744 downregulated the mRNA and protein levels of TGFB1, and in TGF-β1-stimulated normal and severe asthmatic bronchial epithelial cells, miR-744 mimic decreased p-SMAD3 and also increased the protein level of SARA.…”
Section: Asthmamentioning
confidence: 89%
See 1 more Smart Citation
“…Nonetheless, the following are studies that emerged in recent months. In severe asthmatic bronchial epithelial cells obtained from patients, the level of miR-744 was decreased compared to its expression in normal control cells [61]. miR-744 downregulated the mRNA and protein levels of TGFB1, and in TGF-β1-stimulated normal and severe asthmatic bronchial epithelial cells, miR-744 mimic decreased p-SMAD3 and also increased the protein level of SARA.…”
Section: Asthmamentioning
confidence: 89%
“…miR-744 downregulated the mRNA and protein levels of TGFB1, and in TGF-β1-stimulated normal and severe asthmatic bronchial epithelial cells, miR-744 mimic decreased p-SMAD3 and also increased the protein level of SARA. miR-744 decreased the proliferation of bronchial epithelial cells, suggesting the importance of the miRNA in epithelial functions in asthma [61]. miR-943-3p was shown to regulate the level of SFRP4 [62].…”
Section: Asthmamentioning
confidence: 92%
“…Although asthma is commonly diagnosed in childhood, it occurs in all age groups [3]. Ra et al reported that there was no significant difference between the prevalence rate of the elderly (>65) and that of the young people (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) [4]. A lot of stimuli, including cold air and exercise, and other risk factors such as smoking, obesity and rhinitis contribute to asthma incidence [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that dysregulation of the TGF-β1/Smad pathway is necessary for bronchial epithelial cell proliferation in asthma patients. TGF-β1 can initiate cellular response, inducing phosphorylation of Smad2/Smad3 [21]. In addition, miRNAs have been found to implicate in the regulation of TGF-β1/Smad pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation